Under utilization of long-lasting insecticidal nets (LLINs) is challenging malaria elimination program in Ethiopia: a systematic review and meta-analysis - Fekade Demeke Bayou; Natnael Kebede; Yawkal Tsega; Shambel Nigussie; Temesgen Dessalegn Legassu; Amare Muche; Ayana Alebachew Muluneh; Fanos Yeshanew Ayele (BMC, 2024)
Abstract Background Malaria is one of the most common causes of morbidity and mortality in developing countries including Ethiopia. Mass distribution of insecticide-treated nets and indoor residual spray for high malaria risk groups are the major prevention measures in different countries. Achievement of the malaria elimination plan is highly determined by the level of effective utilization of intervention measures. However, there is scarce information showing the national level of insecticide-treated nets utilization. Objective To estimate the pooled prevalence of insecticide-treated nets utilization in Ethiopia, 2023. Method A Systematic Review and Meta-analysis employed to assess the utilization of long-lasting insecticidal nets in Ethiopia. Published articles were searched from Google Scholar, PubMed, Web Sciences, CINAHIL, EMBASE, and Scopus. The collected articles were screened for data extraction and further analysis using preferred reporting items for systematic review and meta-analysis (PRISMA) flow chart. The quality of each study was assessed using the Jonna Briggs Institute (JBI) checklist. The data were extracted using Microsoft Excel and exported to STATA version 17.0 for analysis. The overall pooled prevalence of long-lasting insecticidal nets utilization was determined using a random effects model. Result Out of 1657 articles reviewed, only 21 of them were eligible for final analysis. All of the included studies were used to estimate the pooled prevalence of long-lasting insecticidal net utilization. The point prevalence of LLIN utilization ranged from 14.23 to 91.9%. The Meta-analysis estimated that the overall pooled prevalence of insecticidal nets utilization among all study participants in Ethiopia was 56.26% (95%CI: 44.04-68.48%). Subgroup analysis revealed that insecticidal nets utilization was relatively highest in the Amhara region [63.0, 95%CI (37.0-89.0%)] and during 2020-2023 [61, 95% CI (53.0-69.0%)]. Conclusion Long-lasting insecticidal nets utilization in Ethiopia is lower than the national target plan. Hence, it needs extra follow-up and intervention to enhance its utilization.